Inclusive Public Service Innovation for Persons with Disabilities in Indonesia: An Analysis of Collaborative Governance and Public Value through a Systematic Literature Review - Hastri Ika Nursanti Purnamasari; Ika Devy Pramudiana; Ulul Albab (International Journal of Humanities and Social Sciences Reviews, 2026)
This study examines inclusive public service innovation for persons with disabilities in Indonesia through Collaborative Governance and Public Value perspectives. It responds to the persistent gap between a strong legal framework and uneven implementation, reflected in limited accessibility across local public services. The study applied a Systematic Literature Review using the PRISMA protocol. Twenty Sinta-indexed journal articles published from 2021 to 2026 were selected from 67 Google Scholar records and analyzed through thematic synthesis. The findings classify innovation into four categories: digital services, administrative arrangements, physical and infrastructure improvements, and programs and policies. These initiatives have improved access in several local contexts, but they remain fragmented and lack national integration. Collaborative governance analysis identifies recurring weaknesses in face-to-face dialogue, trust building, commitment to the process, shared understanding, intermediate outcomes, and facilitative leadership. Communication and trust remain limited, commitment is constrained by operational capacity, shared understanding is often normative, and leadership frequently depends on individual initiatives. Public value analysis also shows that efficiency, effectiveness, justice, equality, legitimacy, and public trust have not been achieved consistently because agencies face shortages in human resources, budgets, technology, and accessible infrastructure. Sustainable inclusive innovation therefore requires collaborative processes and public value creation to operate simultaneously. The study recommends operational regulations, dedicated funding, continuous staff training, routine participation of disability organizations, accessible digital and physical service standards, and institutionalized facilitative leadership. These measures can reduce implementation gaps and strengthen equitable public services for persons with disabilities.